Strengthening University Students’ English Grammatical Skills through the Situational Teaching Approach - Wadinlada Thuratham; Sureerat Talapngoen (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2026)
The situational teaching approach (STA) has been applied in EFL instruction for language development in several studies. However, few studies have emphasized English grammatical skills related to verb tenses. To explore the impact of STA on language development, this study aims to 1) examine how STA affects university students’ accuracy in using English verb tenses, and 2) survey students’ perceptions toward the implementation of STA to determine its effectiveness in developing their grammatical skills. The participants in this study were 28 English major students at a public university in eastern Thailand. Data was collected using two instruments: a language achievement test and a questionnaire. The jamovi computer program was employed to analyze the data for mean scores and standard deviations. The results from a paired-sample t-test indicated statistically significant differences between the pre-test and post-test scores of language achievement at the .05 confidence level. This suggests that the STA activities strengthened students’ English grammatical skills across all verb tenses, particularly the present perfect tense, followed by the future simple tense, the present simple tense, the present continuous tense, and the past simple tense, respectively. Furthermore, the questionnaire’s results indicated that students held positive attitudes towards the implementation of STA. Therefore, STA activities can be regarded as effective teaching methods for enhancing students’ proficiency in English verb tenses. Moreover, students perceived the benefits of STA by gaining confidence, increasing vocabulary, promoting interactions, motivating classroom participation, and improving their understanding of English conversations.